Lactoferrin and its Role in Wound Healing - Takayama, Yoshiharu; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
(3z(BLactoferrin and its Role in Wound Healing(3y (Bsummarizes the recent advances of molecular mechanisms of wound healing. It is a complex physiological process that requires the regulation of different types of cells such as immune cells, keratinocytes, fibroblasts, and endothelial cells. Lactoferrin was first identified as an iron-binding glycoprotein abundantly found in milk. It has been considered to play important roles in host defense, since lactoferrin shows broad spectrum of anti-bacterial and anti-viral activities, arising from its iron-chelating property. Furthermore, lactoferrin can regulate the function of innate and adaptive immune cells and exhibits immuno-modulating properties. These activities of lactoferrin implicate that potential use of lactoferrin as a wound healing agent. In addition, this book shows that lactoferrin is a potent regulator of dermal fibroblasts and epidermal keratinocytes, and promotes skin or corneal epithelial wound healing by increasing their proliferation, migration or deposition of extracellular matrix (ECM) components such as collagen and hyaluronan. This book provides the scientific background on use of lactoferrin as a wound healing agent. Indeed, lactoferrin exerts its biological effects by binding to specific lactoferrin receptors on target cells. This book also covers the in-depth information on roles of lactoferrin as a signaling molecule.s
Keywords: Medicine; Human physiology; Biochemistry; Cell receptors; Cytology; Cell membranes; Biomedicine; Biomedicine general; Human Physiology; Cell Biology; Protein Science; Receptors; Membrane Biology